A Correlation between Teachers’ Attitude and Speaking Skills of the ESL Learners: A Study Conducted at BS Level in Rahim Yar Khan - Hameed, Muhammad Muhsin; Zahid, Zohaib (Annals of Human and Social Sciences, 2025)
Teaching English as a Second Language (ESL) presents significant challenges in Pakistan, particularly at the university level. ESL learners often struggle with speaking skills due to limited vocabulary, anxiety, fear of making mistakes, and inadequate teacher motivation. The attitudes of ESL teachers play a crucial role in shaping students' learning experiences and their ability to communicate effectively in English. This study aims to explore the correlation between teachers’ attitudes and the speaking proficiency of ESL learners at the BS level in Rahim Yar Khan. A quantitative correlational research design was employed, involving 250–300 BS-level ESL learners selected through random sampling. Data were collected using a structured questionnaire based on a 5-point Likert scale and a speaking proficiency test assessing grammar, pronunciation, fluency, and vocabulary. Statistical analysis, including Pearson correlation, was conducted using SPSS software to determine the relationship between teacher attitudes and student speaking abilities. A significant correlation between teacher attitudes and students' speaking proficiency. Supportive and encouraging teacher behaviors positively influenced students’ confidence and fluency, whereas negative attitudes hindered language acquisition. The study concludes that fostering a positive and engaging classroom environment can enhance ESL learners' speaking skills. Recommendations include teacher training programs emphasizing motivational strategies and communicative teaching methods to improve language proficiency outcomes.